MicroRNA-183-5p contributes to malignant progression through targeting PDCD4 in human hepatocellular carcinoma - Duan, Xiaohui (Biosci Rep, 2020)
Hepatocellular carcinoma (HCC) remains one of the most common malignant tumors worldwide. The present study aimed to investigate the biological role of microRNA-183-5p (miR-183-5p), a novel tumor-related microRNA (miRNA), in HCC and illuminate the possible molecular mechanisms. The expression patterns of miR-183-5p in clinical samples were characterized using qPCR analysis. Kaplan–Meier survival curve was applied to evaluate the correlation between miR-183-5p expression and overall survival of HCC patients. Effects of miR-183-5p knockdown on HCC cell proliferation, apoptosis, migration and invasion capabilities were determined via Cell Counting Kit-8 (CCK8) assays, flow cytometry, scratch wound healing assays and Transwell invasion assays, respectively. Mouse neoplasm transplantation models were established to assess the effects of miR-183-5p knockdown on tumor growth in vivo. Bioinformatics analysis, dual-luciferase reporter assays and rescue assays were performed for mechanistic researches. Results showed that miR-183-5p was highly expressed in tumorous tissues compared with adjacent normal tissues. Elevated miR-183-5p expression correlated with shorter overall survival of HCC patients. Moreover, miR-183-5p knockdown significantly suppressed proliferation, survival, migration and invasion of HCC cells compared with negative control treatment. Consistently, miR-183-5p knockdown restrained tumor growth in vivo. Furthermore, programmed cell death factor 4 (PDCD4) was identified as a direct target of miR-183-5p. Additionally, PDCD4 down-regulation was observed to abrogate the inhibitory effects of miR-183-5p knockdown on malignant phenotypes of HCC cells. Collectively, our data suggest that miR-183-5p may exert an oncogenic role in HCC through directly targeting PDCD4. The current study may offer some new insights into understanding the role of miR-183-5p in HCC.